Comparison of Complication and Post-Operative Infection Rate Between Application of Carbetocin and Oxytocin during Management of Post-Partum Hemorrhage after Caesarean Section - Choudhury, Farhana Haque; Noor, Mosammat Salma; Tanzin, Syeda Tania; Ahmed, Shahnaz; Fatema, Naheed (Bangladesh Journal of Infectious Diseases, 2023)
Background: Adverse effects can be produced by carbetocin and oxytocin during management of post-partum hemorrhage after caesarean section. Objective: The purpose of the present study was to compare the adverse effects among women with post-partum hemorrhage after caesarean section. Methodology: This randomized controlled trial was conducted in the Department of Obstetrics and Gynaecology at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from July 2015 to December 2015 for a period of six months. Pregnant women diagnosed on the standard criteria admitted in BSMMU, Dhaka, Bangladesh were selected as study population by consecutive type of sampling. Randomization was performed according to computer generated simple random sampling method. An Uterotonic was an agent used to induce contraction or greater tonicity of the uterus. Then the patients were monitored per operatively and post operatively. All the information was recorded in data collection sheet. Main outcome variables were estimated blood loss. Results: A total number of 96 pregnant women were recruited for this study of which 48 cases were enrolled in group I and the rest of 48 case were enrolled in group II. The mean age with SD of the group I and group II were 24.4±4.7 years and 24.7±3.7 years. In blood transfusion of the study patients, 2(4.2%) patients need blood transfusion in group I and 5(10.4%) in group II (p>0.05). One (2.1%) patients had anaemia in group I and 5(10.4%) in group II. Forty-six (95.8%) patients had average menstrual flow in group I and 40(83.3%) in group II (p>0.05). Considering the side effect, 1(2.1%) patients had nausea in group I and 4(8.3%) in group II. Two (4.2%) patients had vomiting in group I and 5(10.4%) in group II. One (2.1%) patients had headache in group I and 4(8.3%) in group II. Four (8.3%) patients had infection rate in group I and 5(10.4%) in group II (p>0.05). Conclusion: In conclusion blood transfusion, anaemia, vomiting and infection rate are found less in group I than group II. Bangladesh Journal of Infectious Diseases, December 2023;10(2):59-64